Importance of basic endurance in triathlon at young age - Balog, A.; Alföldi, Z.; Horváth-Pápai, A.; Ihász, F. (Health Problems of Civilization, 2025)
The study describes the annual training of an international level youth female triathlete who participated in the 2024 European Youth Championships. The aim of the study was to present the distribution of training volume by intensity, sub-sport and time. Training sessions were divided into three intensity zones. The first zone was below the individual anaerobic threshold (IAT), as determined by the Dickuth method. The second intensity zone was between the IAT and the onset of blood lactate accumulation (OBLA), the third zone was above the OBLA. During the 49 weeks, the athlete trained a total of 568.7 hours, which is 11.6±3.7 hours/week (mean ± standard deviation). The training volume for swimming, cycling and running was 203 hours (4.1±1.9 hours/week), 175.8 hours (3.6±2 hours/week) and 149.2 hours (3±1.2 hours/week). 40.3 hours (0.8±0.9 hours/week) were spent on strength training and practicing transitions. In total, swimming, cycling and running training took 463.7 hours (9.5±3.2), 45.6 hours (0.9±0.6) and 19.0 hours (0.4±0.3) in the three intensity zones. The athlete has improved her time and/or ranking in all competitions in which she participated during the previous season. It can be shown that improvements in race results are achievable at youth age with a basic endurance training focus.